2002
DOI: 10.1105/tpc.000943
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Functional Interaction of the Arabidopsis K+ Channel AKT2 and Phosphatase AtPP2CA

Abstract: The AKT2 K ؉ channel is endowed with unique functional properties, being the only weak inward rectifier characterized to date in Arabidopsis. The gene is expressed widely, mainly in the phloem but also at lower levels in leaf epiderm, mesophyll, and guard cells. The AKT2 mRNA level is upregulated by abscisic acid. By screening a two-hybrid cDNA library, we isolated a protein phosphatase 2C (AtPP2CA) involved in abscisic acid signaling as a putative partner of AKT2. We further confirmed the interaction by in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
163
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(175 citation statements)
references
References 76 publications
8
163
0
1
Order By: Relevance
“…Yeast Two-hybrid Assays-The C-terminal region of AKT2 was previously cloned in pGBT9 (48), yielding the (bait) construct named pGBT9-AKT2. The plasmids used for the expression of AKT2 and KAT2 C-terminal regions fused to the GAL4 activation domain (prey constructs) are the previously described plasmids pACT2-AKT2 and pACT2-KAT2 (36,37).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yeast Two-hybrid Assays-The C-terminal region of AKT2 was previously cloned in pGBT9 (48), yielding the (bait) construct named pGBT9-AKT2. The plasmids used for the expression of AKT2 and KAT2 C-terminal regions fused to the GAL4 activation domain (prey constructs) are the previously described plasmids pACT2-AKT2 and pACT2-KAT2 (36,37).…”
Section: Methodsmentioning
confidence: 99%
“…These constructs were used to screen an Arabidopsis thaliana cDNA library prepared with the GAL4 activation domain plasmid pGAD10 (MATCHMAKER, Clontech), using for transformation the lithium acetate method, as described in Chérel et al (48). Transformed cells were spread directly on minimal medium lacking histidine, leucine, and tryptophane (plating medium described in Ref.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that posttranslational regulation is an important mechanism for regulation of K + channel activities in plant cells [13,[38][39][40]. One of the examples is the regulation of AKT1 activity by a protein kinase AtCIPK23.…”
Section: A Complex K + Uptake Regulatory Pathway In Arabidopsis In Rementioning
confidence: 99%
“…These substrates include transcription factors involved in the drought/stress response (Himmelbach et al, 2002), protein kinases such as OST1/SnRK2.6 (Yoshida et al, 2006a), K + channels (Cherel et al, 2002), calcineurin B-like calcium sensors (Guo et al, 2002), a glutathione peroxidase (Miao et al, 2006), and a stress-induced photoprotective plastid protein .…”
mentioning
confidence: 99%